Stages of reckoning : antiracist and decolonial actor training - Mihyang Ginther, Amy (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Stages of Reckoning is a crucial conversation about how racialized bodies and power intersect within actor training spaces. This book provokes embodied and intellectual discomfort for the reader to take risks with their ideologies, identities, and practices and to make new pedagogical choices for students with racialized identities. Centering the voices of actor trainers of color to acknowledge their personal experience and professional pedagogy as theory, this volume illuminates actionable ideas for text work, casting, voice, consent practices, and movement while offering decolonial approaches to current Eurocentric methods. These offerings invite the reader to create spaces where students can bring more of themselves, their communities, and their stories into their training and as fodder for performance making that will lead to a more just world. This book is for people in high/secondary schools, higher education, and private training studios who wish to teach and direct actors of color in ways that more fully honor their multiple identities"--
Keywords: Acting -- Study and teaching; Social justice; PERFORMING ARTS / Theater / History & Criticism; PERFORMING ARTS / Theater / Direction & Production; PSYCHOLOGY / Interpersonal Relations